PRIMARILY MORBIDITY OF RECOVERY WORKERS OF CHERNOBYL ACCIDENT - T. M. Koroleva; V. N. Nurlanov; I. A. Bronstein (Радиационная гигиена)
This paper is devoted to results of comparative analysis of primarily morbidity in two groups of recovery workers of Chernobyl Accident in a period from 1986 up to 2005 years. The groups differed in exposure doses of radiation but identical in age distribution. For the first group the doses were 200-860 mGy (recovery workers of 1986-87 years). The doses of second group didn't exceed 50 mGy (recovery workers of 1988-89 years). Indices of health status in the first group were superior then for the second group practically for every class of Intenational Classification of Disease - 10. Morbidity in the first group was higher then in the second group nearly for all classes of illness. Among all the types of total morbidity, exceeding of neurotic and urinary diseases were statistically significant.